Efficacy of dienogest treatment of clinical symptoms of rectovaginal endometriosis - Papíková, Z; Hudeček, R; Ventruba, P; Szypulová, M (Ceska gynekologie, 2019)
OBJECTIVE: The aim of this prospective, unicentric, cohort study was to evaluate the effect of dienogest use in the therapy of symptomatic endometriosis of rectovaginal septum in patients of fertile age. STUDY DESIGN: Prospective, unicentric, cohort study. SETTING: Department of Obstetrics and Gynaecology, Brno University Hospital and Masaryk University Medical School, Brno. MATERIAL AND METHODS: Prospective analysis of the group of 32 patients in reproductive age who have previously been diagnosed with endometriosis of rectovaginal septum. These patients were treated conservatively with dienogest 2 mg per day during a 24-week period. Through questionnaires and clinical assessment, we have studied the presence of symptoms like dyspareunia, diffuse pelvic pain, Biberoglu-Behrman(B-B) score assessment and subjective pain perception using Visual Analogue Scale (VAS) of pain. Data were collected at the beginning of therapy, after 4, 12 and 24 weeks of dienogest use. RESULTS: Continual use of dienogest during the 24-week period diminishes symptoms of dyspareunia by 62% (p.
Keywords: Rectum; Prospective Studies; dienogest; Humans; Cohort Studies; prospektivní studie; Hormone Antagonists; Vagina; pánevní bolest; Pelvic Pain; dyspareunia; rektum; Endometriosis; nandrolon; endometrióza; vagina; antagonisté hormonů; výsledek terapie; Nandrolone; Treatment Outcome; Pain Measurement; ženské pohlaví; rectovaginal septum; lidé; pelvic pain; měření bolesti; kohortové studie; Quality of Life; kvalita života; Female